Opowieści jako nośnik wartości - na przykładzie historii przekazywanych przez polskich Bukowińczyków - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the presentation is to present the ways in which Polish families, wandering from 17th till 20th centuries, transferred their system of values, by means of oral stories. The population, travelling from Silesia through Čadca region and Bukovina throughout centuries, narrated legends and stories, which were to teach what is bad and is good. The legends, relate both to the supernatural topics (for example, the presence of ghosts among the living, contacts with demon or practicing magic) and to justifications of everyday behaviors (e.g. looking after the elderly, respect for the sacred or the outcome of jealousy.
Keywords: Bukowina; wartości; historie; przekaz ustny; kultura duchowa; Bukovina; values; stories; oral transmission; spiritual culture